1998
DOI: 10.3147/jsfp.33.365
|View full text |Cite
|
Sign up to set email alerts
|

Virus-associated White Spot Syndrome of Shrimp in Taiwan: A Review.

Abstract: White spot syndrome (WSS) is a viral disease which affects most of the commercially cultivated marine shrimp species, not just in Taiwan but globally. The principal clinical sign of WSS is the presence of white spots on the proximal surface of the cuticle of the diseased shrimp. The causative agent is a dsDNA virus which consists of an enveloped, rod-shaped nucleocapsid. White spot syndrome virus (WSSV) infection is character ized by rapid disease onset and high mortality. The mortality typically reaches 90% w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 91 publications
(52 citation statements)
references
References 10 publications
0
49
0
1
Order By: Relevance
“…In recent years, conventional PCR has been routinely used in screening broodstock to be used in hatcheries (Hsu et al, 1999;Muroga, 2001). This tech nique can have false-negative results (Lo and Kou, 1998), and so there is a need for a more sensitive assay than conventional PCR. The present real-time PCR assay to detect and quantify RSIV should be useful for examining cultured fish for the presence of the virus at the early stages of infection because of its higher sensi tivity and specificity than that achieved with conventional PCR.…”
Section: Al 2001)mentioning
confidence: 99%
“…In recent years, conventional PCR has been routinely used in screening broodstock to be used in hatcheries (Hsu et al, 1999;Muroga, 2001). This tech nique can have false-negative results (Lo and Kou, 1998), and so there is a need for a more sensitive assay than conventional PCR. The present real-time PCR assay to detect and quantify RSIV should be useful for examining cultured fish for the presence of the virus at the early stages of infection because of its higher sensi tivity and specificity than that achieved with conventional PCR.…”
Section: Al 2001)mentioning
confidence: 99%
“…As a result, screening of postlarvae (PL) and broodstock for the presence of WSSV has been recommended as part of a strategy to reduce the amount of virus introduced into shrimp farming systems (Limsuwan 1997, Lo & Kou 1998, Withyachumnarnkul 1999. Other proposed methods for reducing the risk of WSD are forma-lin treatment (Limsuwan 1997) and quality assessment tests (Chanratchakool et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The increase in detection rate of PRDV in the receptaculum seminis is caused by the multiplication of the virus during the spawning, probably due to stresses from handling and spawning, or by the reduction in the amount of sperm, which will disturb PCR reaction with insufficient DNA extraction. In P. monodon, it was suggested that infected egg cells are killed by WSBV before maturation (Lo et al, 1997), and that rinse or disinfection of the nauplii is one of the most effective way as a preventive measure of the disease in seed production (Lo and Kou, 1998). How ever, in P. japonicus, it was found that disinfection of the nauplii with povidone-iodine gave a serious damage to their survival (data not shown).…”
Section: Discussionmentioning
confidence: 99%